Contribution of APC and MUTYH mutations to familial adenomatous polyposis susceptibility in Hungary - Papp, Janos (Fam Cancer, 2015)
Familial adenomatous polyposis (FAP) is a colorectal cancer predisposition syndrome with considerable genetic and phenotypic heterogeneity, defined by the development of multiple adenomas throughout the colorectum. FAP is caused either by monoallelic mutations in the adenomatous polyposis coli gene APC, or by biallelic germline mutations of MUTYH, this latter usually presenting with milder phenotype. The aim of the present study was to characterize the genotype and phenotype of Hungarian FAP patients. Mutation screening of 87 unrelated probands from FAP families (21 of them presented as the attenuated variant of the disease, showing <100 polyps) was performed using DNA sequencing and multiplex ligation-dependent probe amplification. Twenty-four different pathogenic mutations in APC were identified in 65 patients (75 %), including nine cases (37.5 %) with large genomic alterations. Twelve of the point mutations were novel. In addition, APC-negative samples were also tested for MUTYH mutations and we were able to identify biallelic pathogenic mutations in 23 % of these cases (5/22). Correlations between the localization of APC mutations and the clinical manifestations of the disease were observed, cases with a mutation in the codon 1200–1400 region showing earlier age of disease onset (p < 0.003). There were only a few, but definitive dissimilarities between APC- and MUTYH-associated FAP in our cohort: the age at onset of polyposis was significantly delayed for biallelic MUTYH mutation carriers as compared to patients with an APC mutation. Our data represent the first comprehensive study delineating the mutation spectra of both APC and MUTYH in Hungarian FAP families, and underscore the overlap between the clinical characteristics of APC- and MUTYH-associated phenotypes, necessitating a more appropriate clinical characterization of FAP families.